Impact of Species Invasiveness on Biodiversity: A Study in the Indian Context - Mondal , Susmita; Pal , Biswajit (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Over the past few decades, anthropogenic activities have emerged as a significant contributor to the decline of indigenous species in their natural habitats. This paper presents an overview of the impact of Invasive Alien Species (IAS) and BT cotton cultivation on biodiversity in India. The methodology employed is rooted in secondary data sources, drawing from various government publications, reports, and BT cotton production records spanning 2002 to 2021. These data sources were carefully analyzed and compared with relevant research reports to fulfill the study's objectives. The findings reveal pronounced invasiveness of species across diverse ecosystems, disrupting ecosystem functions and services, ultimately leading to biodiversity loss with economic implications and health risks. Moreover, BT cotton, introduced as a tool in the agricultural sector, acts as a form of biological invasion. However, it has shown negative repercussions on the environment by affecting non-target organisms and degrading soil health. This study underscores the need to comprehend and address the consequences of these anthropogenic activities for effective conservation and sustainable practices.